Collagen deposition in myocardium after inhibition of fibrinolytic activity - YARAT, AYŞEN (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Proper function of the heart directly depends on the protection of the myocardial architecture. The fibrinolytic system plays an important role(s) in the protection of myocardial architecture and aiding the pumping function of the heart. We investigated the effect of fibrinolytic system inhibition by tranexamic acid (TXA) on cat myocardium and collagen, which are important constituents of the extracellular matrix. Twenty-eight cats (seven per group) were used. Isotonic saline was administered to the control group (C) and TXA (200 mg/kg) diluted isotonic saline given to experimental groups 1 and 2 (El and E2). Experimental group 3 (E3) animals received 100 mg/kg TXA intravenously daily for 7 days. Bloods were drawn from groups C, El, and E2, and fibrinolytic activity was determined by the euglobulin lysis time, fibrinogen degradation products and fibrin plate lytic area diameters. The group C and group El cats were sacrificed following the infusion. The group E2 and group E3 animals were sacrificed at 24 h and day 7, respectively. Light and electron microscopy, along with the collagen contents of the myocardium, were used to examine the myocardial tissues. Electron microscopic examination in groups El and E2 showed inter-myofibrillar edema, glycogen loss, mitochondrial swelling and disorganization of Z-bands, and a decrease of pinocytotic vesicles in capillary endothelial cells. In group E3, increases of Collagen fibrils in intercellular areas and perivascular areas were noted. Biochemical analyses revealed a highly significant collagen accumulation in the myocardium in group E3 (P < 0.01) as compared with group C. These findings suggest that accumulation of the extracellular matrix containing collagen in the myocardium by fibrinolytic system inhibition may be responsible for the abnormal myocardial architecture, leading to cardiomyopathy and altered cardiac function. (C) 2005 Lippincott Williams Wilkins.
Keywords: fibrinolysis; collagen; myocardium; tranexamic acid; cat; TRANEXAMIC ACID; DILATED CARDIOMYOPATHY; ANGINA-PECTORIS; LEFT-VENTRICLE; SUDDEN-DEATH; PLASMINOGEN; INFARCTION; SYSTEM; RAT; HYPERTROPHY